Manajemen Kepemimpinan Daniel - Gandi, Okshe Hana; Tirza Tanzania; Jeldi; Rika Rahayu; Sarmauli (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study aims to determine the leadership principles and values ​​of Daniel, as well as Daniel’s exemplary character as a leader. This study uses a qualitative method with a literature review approach from various secondary data sources collected related to Daniel’s leadership. Based on various definitions of management and leadership put forward by experts and a biblical perspective, it can be concluded that management is the process of organizing, administering, and leading resources efficiently to achieve predetermined goals. Within the framework of Christian leadership, management does not only focus on technical and administrative skills, but also includes faithfulness to faith, integrity, and spiritual impact as demonstrated by biblical figures, especially Daniel. The leadership principles contained in the book of Daniel show that true leaders are those who are faithful to God, rely on and place their full hope in Him, and always strive to learn and live with a clear purpose. Daniel was not only successful in an administrative position, but also serves as a spiritual example that proves that authentic leadership is based on obedience to God. The values ​​embodied in Daniel’s leadership, such as dedication to truth, acknowledging God in every decision, integrity, effective time management, and the courage to defend the faith, demonstrate its relevance to management.